Legal Status of Interfaith Marriage in Indonesia and Its Implications for Registration - Bayu Dwi Widdy Jatmiko; Nur Putri Hidayah; Samira Echaib (Journal of Human Rights, Culture and Legal System, 2022)
Indonesia's marriage law prohibits interfaith unions. However, this provision has not yet taken effect. This study aims to find out how the legal status of marriage is different religions and how the recording provisions are valid in the eyes of the law. This research uses normative legal research methods, with a regulatory approach and data presentation in the form of descriptive analysis. The results of the research show that, first, regarding legal status, interfaith marriage is invalid in the eyes of the law, because it is contrary to the provisions of Law on marriage. However, based on the Supreme Court's decision couples of different faiths can request a court determination, henceforth to continue to carry out the marriage according to the beliefs held by each bride and groom.  Second, regarding the registration of marriages for interfaith marriages, the bride and groom record them with the civil registry office and will be recorded as non-Islamic marriages.